Evaluasi Dampak Terhadap Program Koperasi Simpan-Pinjam Pemberdayaan Perempuan Kepala Keluarga (PEKKA) - Saharani, Debi Rachmi; Walaseci, Dilla Lingga; Maulida, Shinta; Puteri, Annisa; Laura Hapsari, Nawanisyah Maura; Suprapto, Muhammad Fadhli (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2024)
Koperasi Simpan Pinjam PEKKA is an initiative established by Yayasan Pemberdayaan Perempuan Kepala Keluarga (PEKKA). This program aims to empower female heads of households by enhancing their economic capabilities. This study seeks to evaluate the implementation of the PEKKA Cooperative Program using five key indicators: income growth, fulfillment of basic living needs, capital adequacy ratio, capital turnover, loan volume, non-performing loan (NPL) ratio, and member attendance intensity. The research employs a descriptive qualitative approach, incorporating the objective-based and needs-based impact evaluation methods proposed by John Owen. The study findings reveal that the Koperasi PEKKA has been demonstrably successful and has had a positive impact on its members. Indicators such as income growth, capital change, and training participation demonstrate a high degree of success. Meanwhile, other indicators, including capital adequacy ratio, loan volume, and NPL ratio, exhibit moderate success. To further enhance the program's effectiveness, certain regulations require refinement. The cooperative could strengthen its loan repayment regulations and implement more robust sanctions for members who consistently default on their obligations.